Lobbying strategy as a possible response to amorization of active political risk in the company's business - Sporea Danijel (Megatrend Revija, 2022)
The starting point of this paper is given through the issues observed in the part of economic-political business of a company. Every company faces different types of risks during its economic activities. One such risk is political risk, which can affect the company and its business in the country, but also globally.The concept of the paper is a presentation of a thematic study of the concept of political risk limited in the context of the economic-political dimension to the business environment in which the business of a company takes place. In this field, the pressure in the form of specific political risks on the company's operations is multiple, and risk management involves various measures and activities that can potentially reduce their impact. In this context, we believe that lobbying, as a realistic strategic model, can potentially respond to political risks in business. The basis of lobbying arises from the influence on political decision-makers in the process of making various regulations in the field of economic business which in perspective shows a certain degree of company satisfaction, but also the potential to reduce the intensity of political risk. The author tries to use a theoretical approach to explain the strategic approach of lobbying as one of the answers to the disenfranchisement of the political risk of the company's business before any economic investment.